Birth and Breastfeeding in the Hospital Setting during the COVID-19 Pandemic. Issue 1 (January 2021) - Spatz, Diane Lynn; Froh, Elizabeth B.
Abstract : Abstract: For new families giving birth in a hospital setting, the COVID-19 pandemic has presented numerous challenges to their birth, breastfeeding, and postpartum experiences. We present experiences of three first-time, healthy mothers and their babies, as they gave birth in the hospital and were breastfeeding during the start of the pandemic in Philadelphia, PA. Each case is framed in the mother's prenatal goals, infant feeding intentions, birth, breastfeeding, and postpartum experiences. Shared concerns and experiences among the three participants are described in five key areas: 1) Recommendations changing every day, 2) Guilt, concern, and stress, 3) In-person versus telehealth visits, 4) Missing time with family and friends, and 5) Silver linings. Through these mothers' experiences, nurses and other health care providers can learn from their perceptions and events and proactively work to ensure we provide sound anticipatory guidance, enhance our communication, and improve provision of evidence-based lactation care and support. Abstract : In this study, women describe their experiences with being pregnant, getting prenatal care, childbirth education, giving birth, breastfeeding, and newborn visits during the early months of the COVID-19 pandemic. Supportive nursing care and consistent messaging from caregivers were very important to help them handle the stress and uncertainty of the childbirth process in the midst of the pandemic.